2022
DOI: 10.1186/s13018-022-03234-x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of trauma-related acute compartment syndrome of the forearm: a systematic review

Abstract: Objectives Acute compartment syndrome (ACS) can be caused by multiple causes that affect people of different ages. It is considered an orthopedic emergency condition that requires immediate diagnosis and surgical intervention to avoid devastating complications and irreversible damages. This systematic review aimed to present the etiology of trauma-related forearm ACS. Methods A systematic review was performed on four different databases: Embase, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Following our review of the literature, only seven patients who developed compartment syndrome following a fracture were found, with no consistency in the mechanism of injury or type of fracture. In contrast, previous reviews found that fractures were the most common cause of foot, leg, and forearm compartment syndrome [ 45 - 48 ].…”
Section: Reviewmentioning
confidence: 84%
“…Following our review of the literature, only seven patients who developed compartment syndrome following a fracture were found, with no consistency in the mechanism of injury or type of fracture. In contrast, previous reviews found that fractures were the most common cause of foot, leg, and forearm compartment syndrome [ 45 - 48 ].…”
Section: Reviewmentioning
confidence: 84%
“…All seven articles provided relevant evidence of patients’ history of fractures as the main reason for developing ACS [ 5 , 6 , 8 , 11 ] and identified radius, ulna, and both-bone fractures in the arm as the leading risk factors for patients who developed ACS. Overall, 50% of the articles with fracture-related ACS identified both-bone fractures as the most common cause of ACS [ 5 , 11 ]. Table 3 provides detailed information on the prevalence of ACS in distinct fracture types.…”
Section: Reviewmentioning
confidence: 99%
“…Open-arm fractures were contended as a potent cause of ACS due to conflicting logic on how the pressure would build up in an open-arm fracture. However, fractures of the tibia and diaphysis and the arm radius were identified as a common cause of ACS [ 5 , 6 , 8 , 11 ]. Vascular injuries and substance abuse disorders were the least common causes of ACS and were reported in only two of the seven studies included in this review [ 6 , 10 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations